The regional comparison of entrepreneurial traits and entrepreneurial ecosystem in Croatia - Perić, Julia; Koprivnjak, Tihana; Marić, Ivana (Oeconomica Jadertina, 2020)
Entrepreneurs have a key role in building a sustainable and competitive society. Although their success largely depends on themselves and their competencies, the environment in which they find themselves also plays a significant role in their activities. The more developed and stimulating the entrepreneurial ecosystem, the greater the chances that their ideas will also have a positive impact on the quality of life in their community. This paper answers two main research questions: a) whether all entrepreneurs have the same entrepreneurial traits and b) whether entrepreneurial efficiency depends on the development of the environment (region) in which entrepreneurs operate. The paper is based on a comparison of entrepreneurial traits and entrepreneurial environment in Osijek - Baranja and Dubrovnik - Neretva counties. Data obtained by the primary research on a sample of 25 entrepreneurs from Osijek - Baranja and 25 entrepreneurs from Dubrovnik - Neretva County who operate in activities related to tourism were analysed in the empirical section. Based on the conducted analysis, conclusions were made on the impact of entrepreneurial traits and business environment on the efficient business operation of entrepreneurs. The results of this research can serve as a basis for conducting more extensive research by collecting a larger representative sample, but also for new research that will focus on the impact of the degree of regional development on the growth and development of entrepreneurial ventures.